Research Trends in E-tourism: A Bibliometric Analysis using VOSviewer - AWANG, Mesak Yamres (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: This study was conducted to determine (1) the growth of the number of scientific publications in the field of E-tourism, (2) the number of publications per field/subject, and (3) the map of publication development based on keywords and publication year.MethodologyThis study used a quantitative descriptive method with bibliometric analysis. Data was collected by searching through the Google Scholar database with the keyword